(untitled) (Africa Development, 1978)
Contents ARTICLES Fawzi Mansour Some note on social stratification and social change in Africa some theoretical considerations ........................ 5 Résumé ......................... 14 Makhtar Diouf Le problème du développement inégal dans les expériences africaines d'intégration économique .................... 17 Summary ........................ 27 Steve Curry The integration of developed countries and underdeveloped countries through tourism ........................ 29 Résumé ........................ 50 Document TCDC ......................... 51 BOOK REVIEWS Ν.G. Wanjohi Aid and Inequality in Kenya : British Development Assistance to Kenya ........................ 67 FOCUS ON RESEARCH AND TRAINING INSTITUTES The Research Center of Caryounis University, Libya ........................ 75 Institut de Recherches Economiques et Sociales, Université Nationale du Zaïre, Campus de Kinshasa .................... 79